A Collaborative Puzzle Game to Enhance Students’ Fractional Knowledge - Palarao, Vinessa; Palarao, Robert; Salazar, Douglas (Asia Research Network Journal of Education, 2025)
This action research study investigated the effects of trigram puzzle games on the understanding of fractions among high-need 7th graders. The intervention aimed to address students' fractional knowledge and operational skills through engaging and interactive activities such as trigram puzzles. Results showed significant improvements in students' post-test scores compared to their pre-test scores, with several students achieving mastery. The Wilcoxon signed-ranks test confirmed the statistical significance of these improvements, indicating the success of the intervention. Additionally, the study explored student engagement through quantitative measures and qualitative feedback. The positive engagement scores, particularly in the cognitive domain, suggested that the collaborative nature of the trigram puzzles enhanced students' interest, participation, and deep cognitive processing. Focus group discussions further highlighted the supportive and enjoyable learning environment fostered by the trigram puzzles. In summary, the implementation of trigram puzzles games proved to be an effective strategy for improving students' fractional knowledge, addressing misconceptions, and fostering a positive learning experience. The findings suggest that incorporating trigram puzzles as interactive and collaborative activities significantly improves learning outcomes and positively influences student attitudes toward challenging concepts like fractions.